Workshop Manajemen Organisasi dan Penyusunan Modul Dolanan Anak Bagi Forum Taman Baca Masyarakat (FTBM) di Kabupaten Jepara - Sadiyah, Khalimatus; Farida, Yushinta Eka; Saefudin, Ahmad; Hana, May Maulidia; Mahfud, Adam (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to enhance knowledge and expertise in organizational management and children’s play module preparation for the Forum Taman Baca Masyarakat (FTBM) in Jepara Regency. The service used the Participatory Action Research (PAR) method, with the participants being representatives of TBM managers who are members of FTBM. A questionnaire was used as the instrument for evaluating the activity, and the results of which were analyzed descriptively. The service results indicate a significant increase in workshop participants’ understanding. A total of 9 participants (30%) who were initially in the low understanding category succeeded in increasing to the high category, including 18 participants (60%). The workshop activity on preparing children’s play modules also made a positive contribution to the participants, particularly in terms of module preparation. There was a significant increase in understanding, where 10 participants (33.33%) who were initially in the low understanding category succeeded in increasing to the high category, involving 20 participants (66.67%). This activity was successful in achieving positive results and supporting the development of participantsâ€™ skills and understanding of organizational management and module preparation.